A review on the combined toxicological effects of microplastics and their attached pollutants - Mengzhen Li; Wenhao Ma; James Kar Hei Fang; Jiezhang Mo; Lei Li; Min Pan; Rong Li; Xiaoyun Zeng; Keng Po Lai (Emerging Contaminants)
As an emerging environmental pollutant, microplastics (MPs) can adsorb various contaminants, including heavy metals and persistent organic pollutants (POPs). This ability stems from their small size and high specific surface area. Once adsorbed, the adherents can act in combination with MPs to produce synergistic toxic effects when they enter organisms through MPs, exacerbating their toxicity when introduced into organisms. This review examines the toxicological effects of the combination of different MPs and environmental pollutants on terrestrial and marine invertebrates, vertebrates, and microorganisms. In conclusion, the combined toxicological effects of MPs and their attachment to organisms are complex and multilayered. Existing studies have identified certain underlying mechanisms, underscoring the need for societies and governments to account for the combined toxic effects of MPs and their associated pollutants.